Major Histocompatibility Complex–Matched Arteries Have Similar Patency to Autologous Arteries in a Mauritian Cynomolgus Macaque Major Histocompatibility Complex–Defined Transplant Model. Issue 15 (6th August 2019) - Maufort, John P.; Israel, Jacqueline S.; Brown, Matthew E.; Kempton, Steve J.; Albano, Nicholas J.; Zeng, Weifeng; Kelnhofer, Laurel E.; Reynolds, Matthew R.; Perrin, Elizabeth S.; Sanchez, Ruston J.; Slukvin, Igor I.; Thomson, James A.; et al.
Abstract : Background: Arterial bypass and interposition grafts are used routinely across multiple surgical subspecialties. Current options include both autologous and synthetic materials; however, each graft presents specific limitations. Engineering artificial small‐diameter arteries with vascular cells derived from induced pluripotent stem cells could provide a useful therapeutic solution. Banking induced pluripotent stem cells from rare individuals who are homozygous for human leukocyte antigen alleles has been proposed as a strategy to facilitate economy of scale while reducing the potential for rejection of induced pluripotent stem cell–derived transplanted tissues. Currently, there is no standardized model to study transplantation of small‐diameter arteries in major histocompatibility complex–defined backgrounds. Methods and Results: In this study, we developed a limb‐sparing nonhuman primate model to study arterial allotransplantation in the absence of immunosuppression. Our model was used to compare degrees of major histocompatibility complex matching between arterial grafts and recipient animals with long‐term maintenance of patency and function. Unexpectedly, we (1) found that major histocompatibility complex partial haplomatched allografts perform as well as autologous control grafts; (2) detected little long‐term immune response in even completely major histocompatibility complex mismatched allografts; and (3) observed that arterial grafts become almost completely replaced over time with recipient cells. Conclusions: Given these findings, induced pluripotent stem cell–derived tissue‐engineered blood vessels may prove to be promising and customizable grafts for future use by cardiac, vascular, and plastic surgeons.